2018
DOI: 10.1002/uog.19099
|View full text |Cite
|
Sign up to set email alerts
|

Management of pregnancies after combined screening for pre‐eclampsia at 19–24 weeks' gestation

Abstract: In the new pyramid of pregnancy care, assessment of risk for PE at 19-24 weeks' gestation can stratify the population into those requiring intensive monitoring at 24-31 weeks and those in need of reassessment at 32 weeks. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 23 publications
1
38
0
3
Order By: Relevance
“…In a previous screening study at [11][12][13] weeks' gestation, there was no significant difference in median UtA-PI MoM between 196 pregnancies with and 49 898 without major fetal CHD, but, in that study, the values in pregnancies with PE were not reported 5 . Another study at 18-37 weeks' gestation, involving 65 pregnancies with isolated major CHD that did not develop PE and 204 uncomplicated pregnancies delivering phenotypically normal neonates, reported no significant differences in UtA-PI between the two groups 29 .…”
Section: Comparison With Other Studiesmentioning
confidence: 61%
See 2 more Smart Citations
“…In a previous screening study at [11][12][13] weeks' gestation, there was no significant difference in median UtA-PI MoM between 196 pregnancies with and 49 898 without major fetal CHD, but, in that study, the values in pregnancies with PE were not reported 5 . Another study at 18-37 weeks' gestation, involving 65 pregnancies with isolated major CHD that did not develop PE and 204 uncomplicated pregnancies delivering phenotypically normal neonates, reported no significant differences in UtA-PI between the two groups 29 .…”
Section: Comparison With Other Studiesmentioning
confidence: 61%
“…A study of 68 pregnancies with isolated major fetal CHD and 340 normal controls at 11-13 weeks' gestation reported that, in the CHD group, compared to the controls, maternal serum levels of PlGF were lower 4 . This finding was confirmed in a prospective screening study in 50 094 singleton pregnancies at [11][12][13] weeks, which demonstrated that, in the group of 196 pregnancies with isolated major fetal CHD, serum PlGF was reduced 5 . A study of 1 942 072 neonates born in Canada between 1989 and 2012, reported that the prevalence of CHD was higher in infants from pregnancies with than those from pregnancies without PE, and this was particularly so for early PE < 34 weeks' gestation (relative risk (RR), 5.5 (95% CI, 5.0-6.2)) 6 .…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…While aspirin commenced in the first trimester appears to reduce the development of PE, the same intervention seems ineffective when started after 20 weeks. Although it is too late to prevent the development of PE after second‐trimester prediction, the knowledge can still be useful in guiding follow‐up and management of a pregnancy at risk. However, the clinical impact of intensified follow‐up has yet to be proven.…”
Section: Management After Screeningmentioning
confidence: 99%
“…Fourth, the competing‐risks model has been successfully applied for assessment of risk for PE and stratification of pregnancy care by a combination of maternal factors and biomarkers in the first, second and third trimesters of pregnancy. In the first trimester, the competing‐risks approach utilizing maternal factors, MAP, UtA‐PI and PlGF was used to identify women at high risk of developing preterm PE; at a 10% screen‐positive rate, 90% of early‐PE cases and 75% of those with preterm PE were predicted in both a training dataset of 35 948 singleton pregnancies and in two independent, non‐intervention, multicenter studies involving 8775 and 16 451 singleton pregnancies, respectively.…”
mentioning
confidence: 99%